DISTRIBUTION OF HLA POLYMORPHISM IN A SAMPLE OF IRAQI ARABS IN COMPARISON WITH THREE ARAB GULF POPULATIONS - Ad'hiah, Ali (Iraqi Journal of Science, 2024)
The HLA-class I (A and B) and -class II (DR and DQ) alleles were investigated in 145 (72 males and 73 females) unrelated Iraqi Arabs, and their percentage frequencies were compared with the corresponding frequencies in three populations of the Arabian Gulf region (Kuwaitis, Saudis and Omanis). At HLA-A locus, the distribution of the alleles showed no significant difference, while alleles of HLA-B, -DR and -DQ loci showed a significant different distribution in the four populations, especially, B and DR loci. These findings point to differences in the origins of these four distinct Arabic-speaking communities, brought about possibly by an evolutionary recent admixture of the original inhabitants with neighboring and distant populations, although a common ancestor is clear and a later divergence had occurred during evolution.